Atomistic modeling of InGaN/GaN quantum dots-in-nanowire for graded surface-emitting low-threshold, blue exciton laser - Mayada M. Taher; Shahad Al-yousif; Naser M. Ahmed (Results in Physics, 2021)
While the development of the quantum photonics field, including emitter–light coupling using photonic system, has given a lot of attention, it offers quantum control of light. However, the main challenge is coupling to strongly photonic mode localization with nanosystem accuracy. This paper highlights the numerical simulations employed by atomically spin tight-binding model of realistically sized InGaN/GaN dots-in nanowire (NW) architectures. The effects of active region size/shapes, crystal growth directions, graded surface/interface properties, strain relaxation distributions, and polarization-induced potentials on the oscillator strengths of InGaN-based lasers have been investigated. The 3D nanofocused photonic modes, which have been deterministically coupled to multiple quantum dots (QDs) through graded surface/interface technique, have been demonstrated. By using a thin graded layers of a site-controlled pyramidal QDs, the photonic nanofocusing on these QDs at the nonpolar pyramid apex has been geometrically accomplished and successfully leads to stronger characteristics in terms of exciton bandgap energy and polarized emission rate compared to its polar counterpart. For optimum coupling, the nonpolar NW, with intrinsically lower built-in field, exhibits an enhancement of the QDs emission rate as high as 0.98, which is 12% greater than that in a recently reported semipolar MQD structure. The atomistic simulated emission rate for the core QDs buried in NW structure is then incorporated into a TCAD simulator to obtain laser device characteristics. Here, the achievement of truncated pyramid–electrically injected graded surface-emitting laser by nanofocusing the photonic modes formed in InGaN NW has been reported. The nonpolar laser device operates at ~ 402 nm and exhibits a threshold current of ~ 391 A/cm2, which is lower nine order of magnitude lower compared to recently reported semipolar green laser diodes. Our model benchmarking has been done against a reported experiment of polar InGaN disks in GaN NW. Significantly, this engineering innovation proves the viability of InGaN nonpolar quantum dots-in-nanowire architecture as low threshold, high polarized, coherent blue nanoscale lasing emitters, and opens future trends toward a next-generation of electrically injected and interfacial grading-emitting nanolasers operating at high-frequency up to a GHz range.